2014
DOI: 10.1016/j.ypmed.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Association between perceived urban built environment attributes and leisure-time physical activity among adults in Hangzhou, China

Abstract: The present study demonstrated that perceived urban built environment attributes significantly correlate with leisure-time physical activity in Hangzhou, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 28 publications
7
54
2
2
Order By: Relevance
“…Researchers hitherto have not often treated these factors of the built environment, partly because such aesthetic features are relatively hard to quantify. Yet, in a handful of existing studies, scenic routes are found to be preferred by bicyclists (Pikora, Giles-Corti, Bull, Jamrozik, & Rob, 2003;Stefansdottir, 2014;Su et al, 2014). The majority of bicycle trips is motivated by recreational purposes (Goetzke & Rave, 2010;Su et al, 2014), and the attractiveness of the built environment acts as a key factor in bicycle routing (Lovasi et al, 2013;Stefansdottir, 2014).…”
Section: 2mentioning
confidence: 99%
“…Researchers hitherto have not often treated these factors of the built environment, partly because such aesthetic features are relatively hard to quantify. Yet, in a handful of existing studies, scenic routes are found to be preferred by bicyclists (Pikora, Giles-Corti, Bull, Jamrozik, & Rob, 2003;Stefansdottir, 2014;Su et al, 2014). The majority of bicycle trips is motivated by recreational purposes (Goetzke & Rave, 2010;Su et al, 2014), and the attractiveness of the built environment acts as a key factor in bicycle routing (Lovasi et al, 2013;Stefansdottir, 2014).…”
Section: 2mentioning
confidence: 99%
“…Physical inactivity includes leisure-time physical inactivity (LTPI) and non-leisure-time physical inactivity (NLTPI) [14]. Previous studies have found that both LTPI and NLTPI are affected by environmental contexts [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to reduce the burden of CVD risk factors, environmental interventions have become 2 Advances in Epidemiology increasingly recognized as necessary approaches to support behavior change [12]. The fundamental attributes of built environments and community design [13,14] have been linked with increased risk of hypertension and cardiovascular events [15], but only a few studies have evaluated these relationships in an African context [16]. Thus, this study evaluates the association between perceived built environment attributes and the prevalence of hypertension in South African adults in both an urban (Cape Town) and a rural (Mount Frere) context.…”
Section: Introductionmentioning
confidence: 99%